Mitigation of sulphate-reducing bacteria attack on the corrosion of 20SiMn steel rebar in sulphoaluminate concrete using organic silicon quaternary ammonium salt. (10th October 2020) - Etim, Ini-Ibehe Nabuk; Dong, Junhua; Wei, Jie; Nan, Chen; Felix Daniel, Enobong; Babu Subedi, Dhruba; Xu, Dake; Prasad Yadav, Amar; Su, Mingzhong; Ke, Wei
Highlights: Microbial corrosion of 20SiMn steel in sulphoaluminate concrete was studied. SRB can metabolize in sulphoaluminate concrete. SRB accelerates localized corrosion of rebar in sulphoaluminate concrete. OSA was effective in reducing growth of SRB and retards the corrosion of rebar. Abstract: This research was carried out to evaluate the effect of sulphate-reducing bacteria (SRB) on the corrosion of reinforced concrete (RC) using sulphoaluminate cement and also to proffer mitigation measure for reducing the adverse effect of SRB by adopting organic silicon quaternary ammonium salt (OSA) as a bacteriostatic agent. Three different systems were employed for this study: RC with sterilized NaCl (CS), RC with sterilized NaCl and SRB (CS-1), and RC with sterilized NaCl, SRB and OSA (CS-2). The 28 days SRB biofilm growth showed optimized number of sessile cells in the early immersion periods but reduced with extending the time. Consequently, the sessile cells induced the breakdown of the passive film through metabolic reactions of SRB. The corrosion resistance of rebar in different systems reflected by surface morphologies and electrochemical analysis follows the order of CS > CS-2 > CS-1. The proposed mitigation mechanism shows that the silicate component of the OSA adheres on steel surface to prevent the formation of biofilm while the ammonium component adsorbs on SRB cells changing the permeability of bacteria cell wall, reduces the metabolic activities of SRB leading to its death. This implies that OSA played a vital role in reducing the optimized growth of SRB and thus enhances the corrosion resistance of the rebar in concrete.